1999
DOI: 10.1046/j.1365-3156.1999.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary schistosomiasis among schoolchildren in Ibadan, an urban community in south‐western Nigeria

Abstract: SummaryThe current status of urinary schistosomiasis was assessed in Ibadan, an urban community in south-western Nigeria. Of 1331 children examined for eggs of S. haematobium in their urine, 17.4% were infected. Prevalence in postprimary schoolchildren was significantly (P Ͻ 0.01) higher (22.4%) than in primary schoolchildren (12.0%). Intensity of infection based on geometric mean egg count per 10 ml of urine was also higher in postprimary (36.7 eggs/10 ml urine) than primary pupils (29.9 eggs/10 ml urine). Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
30
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 12 publications
11
30
1
1
Order By: Relevance
“…It is therefore of particular note that in the study area, this typical age-related profile of egg-positive cases appeared, being concordant with a typical endemic area. The age-related infection pattern is similar to other studies conducted in Nigeria 18,19 but clearly deviated from other studies that reported significant differences in sex-related prevalence 3 . The lack of association between infection and ages of the subjects could be due to equal dependent on natural water bodies in such low resource community with poor water development.…”
Section: Discussioncontrasting
confidence: 53%
“…It is therefore of particular note that in the study area, this typical age-related profile of egg-positive cases appeared, being concordant with a typical endemic area. The age-related infection pattern is similar to other studies conducted in Nigeria 18,19 but clearly deviated from other studies that reported significant differences in sex-related prevalence 3 . The lack of association between infection and ages of the subjects could be due to equal dependent on natural water bodies in such low resource community with poor water development.…”
Section: Discussioncontrasting
confidence: 53%
“…However, its absence in the canal shows the difficulty of obtaining the exact locations of water contact sites by means of a questionnaire. During the last 20 years, many studies described transmission of schistosomiasis in urban centres in tropical Africa: Bamako (Doumbo et al 1992), Bata (Simarro et al 1990), Bujumbura (Gryseels 1991;Engels et al 1994), Dar Es Salaam (Sarda et al 1985), Harare (Ndamba et al 1994), Ibadan (Okoli & Odaibo 1999), Kampala (Kabatereine et al 1996) *PP, permanent pool; TP, temporary pool (filling period Ͻ 4 months); C, irrigation canal; R, Niger river. † *P Ͻ 0.05; **P Ͻ 0.01; ***P Ͻ 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…In these cities, prevalences were moderate and usually higher in periurban areas than in the centre. However, transmission patterns can vary over time (Gryseels & Ngimbi 1983;De Clercq 1987), and it is still unclear how increasing urbanization and accompanying population growth might affect schistosomiasis transmission (Okoli & Odaibo 1999). In 1998, the overall prevalence of urinary schistosomiasis in the school population of Niamey was low (16%).…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, Schistosoma infection occurs in all human population with prevalence ranging from 9 to 70 % especially in high poverty striking rural areas (Okoli a Odaibo 1999;Mafiana et al 2003;Salawu and Odaibo 2013a, b). Many of these areas had in one time or the other enjoyed mass drug administration either from the local or state government.…”
Section: Introductionmentioning
confidence: 99%